Development and Validation of Spectrophotometric Methods for Simultaneous Estimation of Valsartan and Hydrochlorothiazide in Tablet Dosage Form. (9th January 2014) - Jadhav, Monika L.; Girase, Manoj V.; Tidme, Shripad K.; Junagade, Manish S.
Abstract : Two UV-spectrophotometric methods have been developed and validated for simultaneous estimation of valsartan and hydrochlorothiazide in a tablet dosage form. The first method employed solving of simultaneous equations based on the measurement of absorbance at two wavelengths, 249.4 nm and 272.6 nm, λ max for valsartan and hydrochlorothiazide, respectively. The second method was absorbance ratio method, which involves formation of Q -absorbance equation at 258.4 nm (isoabsorptive point) and also at 272.6 nm (λ max of hydrochlorothiazide). The methods were found to be linear between the range of 5–30 µg/mL for valsartan and 4–24 μ g/mL for hydrochlorothiazide using 0.1 N NaOH as solvent. The mean percentage recovery was found to be 100.20% and 100.19% for the simultaneous equation method and 98.56% and 97.96% for the absorbance ratio method, for valsartan and hydrochlorothiazide, respectively, at three different levels of standard additions. The precision (intraday, interday) of methods was found within limits (RSD < 2 % ). It could be concluded from the results obtained in the present investigation that the two methods for simultaneous estimation of valsartan and hydrochlorothiazide in tablet dosage form are simple, rapid, accurate, precise and economical and can be used, successfully, in the quality control of pharmaceutical formulations and other routine laboratory analysis.